Time Series Modelling using TSMod 3.24 - Charles S. Bos (Tinbergen Institute, 2003)
TSMod is an interactive program which allows the user to estimate a broad range of univariate models. This review describes the possibilities of the package, from a user's perspective and with a secondary focus on the numerical accuracy of the program.
Keywords: C13; C22; C87; 330; Time series; software; econometrics; Zeitreihenanalyse